Testing Label Restrictions on Seeding Timings of Tall Fescue and Kentucky Bluegrass after Herbicide Application - Dani McFadden; Jared Hoyle; Steve Keeley; Zane Raudenbush (Kansas Agricultural Experiment Station Research Reports, 2020)
During a lawn renovation, weeds are often a major problem because they grow more aggressively than seedling turf. Turfgrass seedlings need starter fertilizer and plenty of water for proper establishment, which makes an ideal environment for weeds to thrive as well. With current herbicide label restrictions, there are limited weed control strategies during the critical establishment period. Research trials were initiated in the fall of 2019 in Manhattan, KS, to determine if tall fescue (Schedonorus arundinaceus) and Kentucky bluegrass (Poa pratensis) could be seeded into a stand at different intervals after herbicide application before restrictions on the label. The results showed greater than 90% visual coverage of tall fescue seeded at 0, 3, 7, and 14 days after the application of Trimec Classic, Drive 75 DF, and SedgeHammer. Kentucky bluegrass had over 75% coverage at all seeding intervals when treated with Trimec Classic, Drive 75 DF, as well as plots seeded 3 days after the application of SedgeHammer in the Manhattan, KS, field study.
Keywords: tall fescue; Kentucky bluegrass; seeding; herbicide application